Distribution of power and ordered competition in the European coal and steel community - Vincent Carret (Duke University, Center for the History of Political Economy (CHOPE), 2023)
In the early 1950s, the drive to find a practical solution to European antagonisms led to the construction of the first Common Market at the European scale, between Belgium, France, Germany, Italy, Luxembourg and the Netherlands. At the heart of the Coal and Steel Community, was the idea that shared economic interests would prevent the occurrence of new wars. The institutions created for this purpose led to a new distribution of powers between member states, firms and a supranational power that was tasked to prevent discrimination and organize exchanges between the six countries. By examining the jurisprudence and administrative regulations produced from the early 1950s to the early 1960s, I distinguish between three types of rules grounded in different approaches to competition. This analysis gives a new meaning to the idea of 'ordered competition,' and the sources of inspiration behind the construction of Europe.
Keywords: B25; K21; K23; L11; N44; P48; 330; European Coal and Steel Community; High Authority; Court of Justice; liberalism; administrative state; antitrust; European Coal and Steel Community